Tourism Carrying Capacity: Case Study On Taiping Zoo - Koay, Li Bee (1999)

(untitled)
Development for tourism can be planned to take consideration for protection of the surrounding environment and for the attainment of an equilibrium or ideal balance . This can be achieved through incorporation of effective management and planning tools such as the carrying capacity concept. Current available literature on the concepts of carrying capacity did not specifically discuss its use and relevance in a tourism development such as a zoological park. Hence, this case study was conducted on the carrying capacity of such a development, the Taiping Zoo. This study aims to promote tourism carrying capacity studies as a n important consideration to be incorporated into future management plans of the Taiping Zoo. It also advocates that the concepts and principles of tourism carrying capacity be more widely accepted and utilized in modern day zoological park operations.